Synthesis of new derivatives of hydrochlorothiazide containing diazonium groups and study of their biological activity - Al-Sahib, Sanaa A.; Hussein, Iftikhar Ahmed; Abdulridha, Myasim Qasim; Albanaa, Miami Abdulaleem (Pharmakeftiki, 2025)
Diazonium salts are highly reactive compounds that serve as intermediates in numerous chemical reactions. In this study, they were synthesized and subsequently allowed to react with phenolic drugs, ethyl acetoacetate, and acetylacetone in order to yield compounds M1–M5. Following further processing in order to produce compounds M6 and M7, compounds M4 and M5 interacted with hydrazine hydrate, resulting in an 80% conversion. The synthesized compounds (M1–M7) were characterized through an analysis of their physical properties, nuclear magnetic resonance spectra, elemental composition, and infrared spectra. The biological activities of the same compounds were also evaluated against various bacterial strains (i.e., Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Serratia marcescens, Morganella, Acinetobacter, Salmonella, and Streptococcus pneumoniae) and a yeast species (Candida albicans), using the agar well diffusion method.